A qualitative analysis of military couples with high and low trauma symptoms and relationship distress levels - Wick, Stephanie; Goff, Briana S. (My University, 2014)
The purpose of the current study was to understand the experiences of a subset of military couples regarding the effects of war deployment on couple functioning. This study utilized the core “couple functioning” variables included in the Couple Adaptation to Traumatic Stress Model (Nelson Goff & Smith, 2005) as sensitizing concepts to guide the qualitative analysis process. Participant interviews (n = 15 couples, 30 total participants) were divided into subgroups according to high and low trauma symptom and relationship satisfaction scale scores. Five primary themes were identified in the results: communication, conflict management, roles, support/nurturance, and post-traumatic growth. Overall, highly satisfied couples and those with the lowest levels of traumatic stress symptoms reported more positive relationship functioning in the identified areas, while couples reporting higher traumatic stress symptoms and lower relationship satisfaction indicated varied or inconsistent qualitative results. Clinical and research implications for military couples also are identified.
Keywords: Military couples; Couple functioning